Development of an automated millifluidic platform and data-analysis pipeline for rapid electrochemical corrosion measurements: A pH study on Zn-Ni. (1st October 2022) - Joress, Howie; DeCost, Brian; Hassan, Najlaa; Braun, Trevor M.; Gorham, Justin M.; Hattrick-Simpers, Jason
Abstract: We describe the development of a millifluidic based scanning droplet cell platform for rapid and automated corrosion. This system allows for measurement of corrosion properties (e.g., open circuit potential, corrosion current through Tafel and linear polarization resistance measurements, and cyclic voltammograms) on a localized section of a planar sample. Our system is highly automated and flexible, allowing for scripted changing and mixing of solutions and point-to-point motion on the sample. We have also created an automated data analysis pipeline. Here we demonstrate this tool by corroding a plate of electroplated Zn 85 Ni 15 alloy over a range of pH values and correlate our results with XPS measurements and literature.